Construction and testing of a single molecule AFM and applying it to study mechanical properties of notch proteins - Dey, Ashim (Kansas State University, 2010)
For proteins in living cells, forces are present at all levels. These range from macroscopic to single molecule levels. Single molecule atomic force microscopy (AFM) in force extension (FX) and force clamp (FC) modes can investigate the mechanical properties of proteins, for example, forces at which proteins unfold, or the kinetics of these processes. In the FX-AFM experiments, proteins are pulled at constant velocity, while in FC-AFM experiments, proteins are pulled at constant force. This thesis describes i) how a single molecule FX/FC-AFM was constructed using various components, ii) how it was calibrated and tested using (I27)4 polyprotein, and iii) how it was applied to the studies of a Notch construct. Building up the single molecule FX/FC-AFM system opened a path to investigate the mechanical properties of proteins. Such a system was tested on a known protein construct, hence the usage of the (I27)4 polyprotein. The Notch protein is a signaling protein that plays a role in triggering breast cancer. It is believed that understanding the mechanical properties of Notch can help to understand its oncogenic functions. We have successfully constructed and calibrated the FX/FC-AFM setup. It was found that the AFM worked for the standard calibration protein of (I27)4. The results on a Notch construct revealed our ability to see some conformational transition state in this molecule under force. These results opened a path for further investigations of a Notch construct at various physiologically relevant conditions.
Keywords: Force spectroscopy; Atomic force microscopy; Notch protein; Biophysics, General (0786)